2014
DOI: 10.1371/journal.pbio.1001942
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hypermutagenesis Accelerates the Evolution of Legume Endosymbionts following Horizontal Gene Transfer

Abstract: Stress-responsive error-prone DNA polymerase genes transferred along with key symbiotic genes ease the evolution of a soil bacterium into a legume endosymbiont by accelerating adaptation of the recipient bacterial genome to its new plant host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 67 publications
0
62
1
Order By: Relevance
“…We found that plant compounds enhance HGT and initiate the nodulation process that ensures massive and specific multiplication, through the interaction with ICElocated regulatory genes. Interestingly, it was recently shown that the dissemination of symbiotic plasmids to different taxa is assisted by error-prone DNA polymerases encoded in the transferred element, which are more active in the plant environment (43). Altogether, these observations support the view that both the plant and the symbiosis element manipulate in concert with the bacterium (8).…”
Section: Discussionmentioning
confidence: 68%
“…We found that plant compounds enhance HGT and initiate the nodulation process that ensures massive and specific multiplication, through the interaction with ICElocated regulatory genes. Interestingly, it was recently shown that the dissemination of symbiotic plasmids to different taxa is assisted by error-prone DNA polymerases encoded in the transferred element, which are more active in the plant environment (43). Altogether, these observations support the view that both the plant and the symbiosis element manipulate in concert with the bacterium (8).…”
Section: Discussionmentioning
confidence: 68%
“…All findings in this study from the PU‐HPC bipartite network analysis underscore the importance of undertaking subsequent sequencing and experiment projects in resolving the issue concerning genomic annotation and interaction of rhizobial plasmids (diCenzo et al ., 2014). Further work aimed at identifying the selective forces acting on both symbiotic and accessory plasmids and responsible for variation in nitrogen fixation efficiency should also help in understanding their co‐evolutionary framework ruling the evolution of Rhizobium ‐legume symbiosis (Remigi et al ., ). Given the increasing availability and utilization of multiomics sequencing with the rapid development of network analysis approaches, such as multipartite network and multilayer network, we can expect to better understand these intriguing genetic elements in various lifestyles of all rhizobial bacteria (diCenzo et al ., ; Marx et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In a particularly notable case, interspecies transfer of a symbiotic plasmid was coupled with laboratory evolution in an ongoing attempt to yield a symbiosiscompetent strain. The researchers established Ralstonia solanacearum (a plant pathogen) carrying the symbiotic plasmid of the rhizobium species Cupriavidus taiwanensis as the test system (Marchetti et al 2010(Marchetti et al , 2014Guan et al 2013;Remigi et al 2014;Capela et al 2017). Although initially unable to form nodules, adaptive mutations, such as in the type III secretion system, were identified that allowed for nodulation to occur (Marchetti et al 2010).…”
Section: Large-scale Genome Manipulationsmentioning
confidence: 99%